Effects of repetitive paired associative stimulation on brain plasticity and working memory in Alzheimer's disease: a pilot randomized double-blind-controlled trial. (16th March 2023) - Kumar, Sanjeev; Zomorrodi, Reza; Ghazala, Zaid; Goodman, Michelle S.; Blumberger, Daniel M.; Daskalakis, Zafiris J.; Fischer, Corinne E.; Mulsant, Benoit H.; Pollock, Bruce G.; Rajji, Tarek K.
ABSTRACT: Design: Pilot randomized double-blind-controlled trial of repetitive paired associative stimulation (rPAS), a paradigm that combines transcranial magnetic stimulation (TMS) of the dorsolateral prefrontal cortex (DLPFC) with peripheral median nerve stimulation. Objectives: To study the impact of rPAS on DLPFC plasticity and working memory performance in Alzheimer's disease (AD). Methods: Thirty-two patients with AD (females = 16), mean (SD) age = 76.4 (6.3) years were randomized 1:1 to receive a 2-week (5 days/week) course of active or control rPAS. DLPFC plasticity was assessed using single session PAS combined with electroencephalography (EEG) at baseline and on days 1, 7, and 14 post-rPAS. Working memory and theta–gamma coupling were assessed at the same time points using the N-back task and EEG. Results: There were no significant differences between the active and control rPAS groups on DLPFC plasticity or working memory performance after the rPAS intervention. There were significant main effects of time on DLPFC plasticity, working memory, and theta–gamma coupling, only for the active rPAS group. Further, on post hoc within-group analyses done to generate hypotheses for future research, as compared to baseline, only the rPAS group improved on post-rPAS day 1 on all three indices. Finally, there was a positive correlation between working memory performance and theta–gamma coupling. Conclusions: This study did not show a beneficial effect of rPAS for DLPFC plasticity or working memory in AD. However, post hoc analyses showed promising results favoring rPAS and supporting further research on this topic. (Clinicaltrials.gov-NCT01847586)